ChemInform Abstract: Catalytic, Enantioselective, Intramolecular Carbosulfenylation of Olefins. Issue 39 (5th September 2013) - Denmark, Scott E.; Jaunet, Alex
Abstract For the first time a catalytic enantioselective carbosulfenylation of alkenes with an aromatic nucleophile is presented.